Major Supply Chain Challenges in the Era of Heavily Concurrent Industrial Processes: An Integrated Supply Chain Management 4.0 Framework - Dourado, João Paulo; Araújo , António; Ferreira , Ana Cristina; Silva , Rui (Management and Production Engineering Review, 2026)
This study aims to comprehensively examine the supply chain management concept, starting from its fundamental principles and delving into the primary hurdles hindering its effective implementation alongside exploring the latest emerging trends. Key challenges include fostering innovation and robust partnerships for supply chain management, seamlessly integrating new product development and concurrent engineering processes. Furthermore, current trends underscore the imperative of achieving sustainability within supply chain frameworks, striving to cultivate flexibility and resilience. Supply chain management should be aligned with environmentally conscious practices ("green" initiatives) embracing the transformative potential of Technology 4.0 to usher in the era of Industry 4.0. A review of existing literature regarding the implementation of supply chain management was carried out seeking to identify best practices. Based on the literature analysis and through content analysis methodology notable gaps have been discerned where further exploration is warranted particularly concerning the evolving supply chain management, sustainability, green supply chain management initiatives and the integration of Technology 4.0. These areas present opportunities for deeper investigation to provide pillars for future advancements in supply chain management practices. Research demonstrates that organizations must prioritize the integration of information-based systems to support supply chain management as well as the need for risk assessment. A framework is proposed in six parts bridging the domains of Industry 4.0, concurrent engineering and supply chain management. By aligning technology and process design it is possible to conceptualize and measure the true impact of Industry 4.0 on performance.